Investigation of large-scale structures in turbulent boundary layer and their detections by wall-based sensors array - Rkiouak, Noura (2020)
Only limited DNS and experimental information about the interaction between wall skin-friction fluctuations and large-scale structure is available. The ability to gain insight into this interaction experimentally is substantial. This research study presents results of an experimental investigation to study stereoscopic PIV by highlighting the results obtained with s-PIV in comparison with the one obtained by hot-wire (HW) sensors. It is followed the investigations of Reynolds numbers that are lower than available prior experimental and span the DNS and experimental ranges in the literature. It ends on the experimental investigation, at Reτ = 568, of the effects of large-scale structures on wall shear-stress fluctuations. Both, flow visualisation and hot-wire anemometry are used simultaneously to investigate their correlation. The idea is to use the signals from a rake of twenty hot-wire sensors placed at the wall, to reconstruct the instantaneous profile of the skin-friction fluctuation. By projecting this signal in time and using Taylor’s hypothesis a view of the mapping of the instantaneous skin-friction is obtained in the x-z plane. By using stereoscopic PIV, a map of the large scale-structure in the log-region is captured and analysed to identify the large-scale structures in the log-outer regions. Data are taken simultaneously between hot-wire sensors and s-PIV, to obtain information from a map of fluctuating skin-friction signal at the wall together with the large-structure in the log-region. It is shown that large-scale structures exist in the log layer and that they certainly contribute to structures at the wall. Moreover, it is revealed that large-scale structures exist even in the skin-friction fluctuations, which are essentially associated with the large-scale structures in the log layer. Indeed, similarities between the patterns from instantaneous skin-friction map at the wall and the velocity map in the buffer and logarithmic regions are found.